TINJAUAN VARIASI TEBAL GROUTING SIKADUR® 31 CF NORMAL Dan PANJANG PENYALURAN TERHADAP DAYA LEKAT BAJA TULANGAN PADA BETON MUTU NORMAL - Anis Rosyidah; Gilang Maulid R; Efendi Yasin (Jurnal Poli-Teknologi, 2011)
Abstract One of the requirements in reinforced concrete structures is the existence of bonding between reinforcement and concrete, so that if the concrete structure of the given load will not slip between reinforcing steel and concrete, with a condition for disbursement length and diameter sufficient reinforcement. This research was conducted with laboratory experimental methods, this study used threaded steel bars 10 mm in diameter grown on cylindrical concrete specimens with a length variation of normal quality distribution of 100 mm and 200 mm, and for thickness variation Sikadur® 31 CF Normal used a thickness variation mm, 2 mm, 3 mm. Each specimen is tested with a method of "bond, a pull-out test". Based on the results obtained from voltage variations thick adhesive Sikadur® 31 CF Normal, with thick sticky voltage Sikadur®31 CF Normal 2 mm produces voltage optimium closely with the value of 8.412 MPa,the adhesive stresses are found for the distribution of the required length of 182.860 mm for thickness variation Sikadur® 31 CF Normal 1 mm, 97.586 mm for thickness variation Sikadur® 31 CF Normal 2 mm, while for thickness variation Sikadur® 31 CF Normal 3 mm can not be calculated and analyzed the test results because of the "bond, a pull-out" no reinforcing steelreaches the yield condition, caused by broken concrete and reinforcing steel cylinder apart before reaching the yield condition. Then the length distribution obtained by the above formula Park & Paulay compared with the length distribution of article 14.2 of SNI 30-2847-2002 obtained epoxy ratio of 2:13 for the thickness of 2 mm with a planting of 100 mm. In the epoxy thickness 1 mm with 200 mm obtained planting 2:7 ratio, and the planting of monoliths obtained 2:5 ratio. Bold use of Sikadur® 31 CF Normal apparently affect the pattern of damage to the concrete and steel. When planting steel bars are too short we need a thicker epoxy, planting reinforcement 100 mm with a thickness of 3 mm epoxy. When planting longer needed a thinner epoxy, the planting of 200 mm reinforced epoxy with a thickness of 1 mm. Based on the pattern of damage that occurs, the thickness of epoxy should consider the quality of concrete used to prevent the destruction of the concrete. Keyword: grouting thickness, development length, bond stress.